A213 DETERMINING TRANSITION READINESS IN INFLAMMATORY BOWEL DISEASE (TREAD-IBD): A MULTI-CENTRE CROSS SECTIONAL STUDY. (1st March 2018) - Foster, A; Bressler, B; Carroll, M W; deBruyn, J; El-Matary, W; Fu, Y; Huynh, H Q; Kroeker, K I; Lawrence, S; Seow, C; Wine, E; Jacobson, K
Abstract: Background: Transitioning inflammatory bowel disease (IBD) patients from pediatric to adult care is a challenging and complex process. Knowledge of the potential factors influencing transition readiness is limited, especially in this unique population. Aims: To evaluate potential factors including patient and parent psychosocial wellbeing, self-management, self-advocacy skills and geographical location of medical care, and to explore their effects on transition readiness in patients with IBD. Methods: An ongoing cross-sectional multicentre study evaluating transition readiness in IBD patients 16 to 19 years of age who have been enrolled from pediatric and adult gastroenterology clinics in Western Canada (Vancouver, Calgary, Edmonton and Winnipeg). Questionnaires include the OnTRAC Readiness Assessment Questionnaire, the Screen for Child Anxiety Related Disorders (SCARED), the Patient Health Questionnaire (PHQ-8) to screen for depression and the Generalized Anxiety Disorder (GAD-7) to screen for parental anxiety. The patient, parent and physician also score the child and parent's readiness to transition on a scale of 1–10 (1=not ready and 10=completely ready). Results: To date, 31 patients have been enrolled from participating Vancouver sites, 24 with Crohn's disease, 4 with ulcerative colitis and 3 with indeterminate colitis. Questionnaires indicated scores consistent with an anxiety disorder in 38% of those with IBD (only 20% of parents suggested anxiety in their child), and mild to severe depression in 23% of those with IBD. In addition, 24% of the parents themselves had GAD-7 scores consistent with mild to severe anxiety. Patients reported a mean readiness to transition score of 7.4. The physicians' evaluations of readiness to transition was similar to the patient group (mean 7), while the parent group gave a lower score (mean 5.8). Indeed, 77% of patients never or rarely saw the physician on their own at visits, 59% of parents indicated that they call the healthcare team with disease-related questions or concerns for their child and 46% of patients need reminders from parents to take medications. Conclusions: Survey data from initial recruited patients suggest that a large proportion of transitioning youth continue to have behaviours that reflect a lack of self-advocacy and independence. In addition, depression and anxiety scores are high in this population which could impact the level of preparation for transition to adult care. Further data will be collected in this ongoing multi-centre study to assess the impact of youth and parental factors on transition readiness and to evaluate possible site to site variability. Funding Agencies: Janssen Pharmaceuticals